Bone regeneration and infiltration of an anisotropic composite scaffold: an experimental study of rabbit cranial defect repair. Issue 4 (3rd March 2016) - Li, Jidong; You, Fu; Li, Yubao; Zuo, Yi; Li, Limei; Jiang, Jiaxing; Qu, Yili; Lu, Minpeng; Man, Yi; Zou, Qin
Abstract: Tissue formation on scaffold outer edges after implantation may restrict cell infiltration and mass transfer to/from the scaffold center due to insufficient interconnectivity, leading to incidence of a necrotic core. Herein, a nano-hydroxyapatite/polyamide66 (n-HA/PA66) anisotropic scaffold with axially aligned channels was prepared with the aim to enhance pore interconnectivity. Bone tissue regeneration and infiltration inside of scaffold were assessed by rabbit cranial defect repair experiments. The amount of newly formed bone inside of anisotropic scaffold was much higher than isotropic scaffold, e.g., after 12 weeks, the new bone volume in the inner pores was greater in the anisotropic scaffolds (>50%) than the isotropic scaffolds (<30%). The results suggested that anisotropic scaffolds could accelerate the inducement of bone ingrowth into the inner pores in the non-load-bearing bone defects compared to isotropic scaffolds. Thus, anisotropic scaffolds hold promise for the application in bone tissue engineering.